Addis Ababa’s sefer, iddir, and gebbi - Anteneh Tesfaye Tola (A+BE: Architecture and the Built Environment, 2023)
This research is motivated by the scholarly calls for new concepts and analytic tools for documenting, analysing, and theorizing complex urban territories such as those of cities in Africa. With implicit comparative intent, it takes the case of Addis Ababa city and its old and typifying places—the sefer, to develop and test a new architectural transdisciplinary research methodology referred to as the trinocular. By way of this methodology, it unearths and introduces sefer, iddir, and gebbi of Addis Ababa as not only socio-spatial phenomena but concepts and vocabulary for a located and nuanced reading of the city itself. Sefer are introduced as flexible boundary conditions that are primarily cognized by their dwellers—results of indigenous and autochthonous foundation and continued processes of self-actualization by communities that construct them. Iddir is unearthed as a form of social capital embedded in sefer that appears in the structures of relations among residents. And the gebbi as an urban spatial typology that constitutes the sefer’s morphology—the last frontier of communality just prior domestic spaces which, in many cases, can be a single multi-functional room.